(untitled) (Archives of Mechanics - Test, 1997)
The paper presents a derivation of the Hashin—Shtrikman bounds for the plane elasticity problems and for the Kirchhoff problem of plates in bending. A two-dimensional counterpart of the method of FRANCFORT—MURAT [1] is applied. The method consists of three subsequent layerings along the directions of vertices of a unilateral triangle.